The Role of Nursing in Promoting Community Health Through Health Awareness Campaigns - Albogami, Fatimah Mefres Jasar; Alshammri, Salma Mohana; Alanazi, Masheal Ashwi Sahal; Alenezi, Manal Khalaf; Alanzi, Latifa Mutred; Alanazi, Hana Khalaf; A. Alanezi, Reigh Abdulhadi; Alshehri, Azzah Humdei; Albawah, Shamah Mohamed Ahmed; Alanzi, Hadeel Athal (Journal of Ecohumanism, 2024)
Improving overall population well-being. Among healthcare professionals, nurses play a particularly influential role due to their accessibility, trustworthiness, and ability to interact directly with diverse populations. Beyond their clinical responsibilities, nurses are increasingly recognized as educators and advocates who facilitate the adoption of healthier lifestyles through targeted health awareness campaigns. This paper explores the pivotal role of nursing in promoting community health by analyzing the effectiveness, challenges, and opportunities of nurse-led health awareness initiatives. A review of existing literature reveals that campaigns facilitated by nurses—focusing on issues such as diabetes prevention, smoking cessation, obesity management, and vaccination awareness—have demonstrated significant improvements in public knowledge and behavioral outcomes. Nurses’ involvement in schools, workplaces, and community centers further highlights their capacity to instill preventive health practices across different age groups and social settings.